Mental Health Matters: School Contribution in Strengthening Mental Health - Putri, Luqyana Azmiya; Ichsan, Ichsan; Alamin, Nurul; Annisyaa', Nur (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2023)
Mental health is one of the essential aspects that should be watching out in student evolution proccess. The growths of a student contain frustation and over learning pressure vulnurable to cause mental disorder occur to student. Occerences of mental issue occurr everywhere. For instance, based on the result of KPPA survey in 2020, retrieved almost 3.200 (13%) student of elementary school and students of senior highschool from 34 provinces in Indonesia undergo symptoms depression both mild to severe tiers. Therefore, refer to that issues, this article aims to describe school contribution to strenghtening students mental health. The method of this research uses library research. The result shows that there are several measures which are using by school to amplifing mental health. First, through learning strategy. Second, provisioning counseling guidance services. Fourth, giving motivation to students. The last one is giving time to take a break.